ANALYSIS OF THE USE OF SOCIAL MEDIA AS A HOTEL CULINARY TREND PROMOTION MEDIA FOR GEN Z - Hastiningsih, Wahyu Tri; Sari, A.Anditha (LPPM Universitas Duta Bangsa Surakarta, 2023)
One type of trend that is experiencing rapid development is culinary tourism. Culinary trends make food like a subject and a medium. The high demand for culinary makes this trend have good market prospects, especially for Generation Z. It is necessary to carry out studies related to hotel culinary trends to find out the characteristics and behavioral characteristics of Generation Z so that they can provide references regarding appropriate marketing strategies. An understanding of the nature and characteristics is needed to design messages or content for hotel culinary promotions more effectively. This research was conducted using a quantitative method where the data obtained was obtained from a survey method using online questionnaires through the Google form application. The questions given contain characteristics, sources of information variables, and gen Z behavior variables towards hotel culinary. The target for distributing the questionnaires was Generation Z who came from the island of Java. The distribution of questionnaires is used to measure responses from respondents and facilitate researchers in measuring data. Gen Z respondents in Java are dominated by women, aged 19-21 years, and students. Most of the Gen Z respondents had stayed at a hotel with a frequency of more than 2 times and stayed for 1 to 2 nights. Hotel culinary information is easily obtained through social media and is a consideration for staying at the hotel. Location and price are factors that Gen Z considers when choosing a hotel. The content and aspects that most influence culinary purchases are promos, tastes, and reviews from previous guests. The package menu that is popular with Gen Z is a buffet with a payment method that is often used, namely cash. The promos that are most in demand and affect the purchase of hotel culinary delights for Gen Z are discount vouchers and buy 1 get 1 promo. The hotel's culinary delights for Gen Z are food from Indonesia, coffee or tea drinks, and salty or sweet snacks. Gen Z prefers to make culinary as a basic need to survive and meet the energy needs to be used in daily activities.